(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
The aim of this paper is to analyze and discuss the verbal and iconic representations of book and alphabetic writing, conceived as western artifacts of ideological content, which impregnated Andean culture of the 17th century. I examine the occurrences of objects/acts in documents of indigenous origins, such as those produced by Inca Garcilaso de la Vega, the compiler of Manuscrito de Huarochirí, Titu Cusi Yupaqui, and Felipe Guamán Poma de Ayala. The context ―where such artifacts appear in these documents― reveals how Andeans perceived new concepts, and assimilated them in order to utilize them for their own objectives within the early colonial society.